STRATEGI MENURUNKAN PRAVELENSI GIZI KURANG PADA BALITA - kabira, fredy (Media Keperawatan:Politeknik Kesehatan Makassar, 2020)
Fulfillment of toddler nutrition is closely related to the structure of family functions in the practice of fulfilling nutrition through the Family Centered Care (FCC) system in collaboration with parents and professionals. The results of monitoring Nutrition Status in 2017, the percentage of undernutrition in West Sulawesi province was 19.9%. Polewali Mandar District, 19% under-nutrition, was in position 4 out of 6 districts. Strategies carried out in empowering families to fulfill nutrition for children under five are providing health education, conducting counseling, making food modifications and coaching mothers of under-five nutrition. The research objective was to determine the effect of strategies / interventions to reduce the prevalence of under-five malnutrition. The research was conducted in the Village of Rumpa and Buku, Mapilli, Polewali Mandar, West Sulawesi. Research on 27 July-05 September 2020. Quantitative research method quasi-eksperimental design. Data were processed using statistical analysis Independent Sample t Test and Paired Sample t Test with a significance level of Î± = 0.05 for treatment, 70 respondents each group of 35 people. The results of the treatment group study experienced significant changes while the control group did not show any significant changes.Â